The Impact of Covid-19 on Indonesian Muslim Pilgrimage - Maharani Alifah Dhiya Rahmadhanitya; Sidik Jatmika (Millah: Journal of Religious Studies, 2021)
This article describes the impact of postponement of Umrah and Hajj towards Indonesia during Covid-19 pandemic. The bilateral relations between Saudi Arabia and Indonesia have been going on for a long time. Hajj and Umrah visits are one way to establish bilateral cooperation between Indonesia and Saudi Arabia. During pandemic, Saudi Arabia make a foreign policy to postponement Umrah and Hajj, this policy make Indonesian Muslim unable to pilgrimage Umrah and Hajj. This postponement will impact Indonesia in many sectors. The research method used in this study is a descriptive study and library research aims to understand the reasons for a state to make a foreign policy and understand the impact of these policies towards Indonesia. Islamic Jurisprudence (Fiqh) concept, Foreign Policy theory, and Foreign Policy Impact Theory are used to analyze the impact of postponement Hajj and Umrah. The findings confirm that the actors that felt the impact were the government, Hajj and Umrah travel agents, and also the Hajj and Umrah pilgrims from Indonesia.